Plank Times and Lower Extremity Overuse Injury in Collegiate Track-and-Field and Cross Country Athletes - Lace E. Luedke; Mitchell J. Rauh (MDPI AG, 2022)
Trunk muscle endurance has been theorized to play a role in running kinematics and lower extremity injury. However, the evidence examining the relationships between static trunk endurance tests, such as plank tests, and lower extremity injury in athletes is conflicting. The purpose of this study was to assess if collegiate cross country and track-and-field athletes with shorter pre-season prone and side plank hold times would have a higher incidence of lower extremity time-loss overuse injury during their competitive sport seasons. During the first week of their competitive season, 75 NCAA Division III uninjured collegiate cross country and track-and-field athletes (52% female; mean age 20.0 ± 1.3 years) performed three trunk endurance plank tests. Hold times for prone plank (PP), right-side plank (RSP) and left-side plank (LSP) were recorded in seconds. Athletes were followed prospectively during the season for lower extremity overuse injury that resulted in limited or missed practices or competitions. Among the athletes, 25 (33.3%) experienced a lower extremity overuse injury. There were no statistically significant mean differences or associations found between PP, RSP or LSP plank test hold times (seconds) and occurrence of lower extremity overuse injury. In isolation, plank hold times appear to have limited utility as a screening test in collegiate track-and-field and cross country athletes.